Maxim violation in archie comic - Dewi, Angreni Saraswati (LingTera, 2017)
This research study aims at describing: the forms of the violation of cooperative maxims; the violation of politeness maxims used in Archie speech situation, and the way to understand maxim violations that makes the reading of the comic easier. This study used two data collection methods, namely reading comprehension and note-taking. The result of this study reveals that there is a violation of maxims both co-operative and politeness maxims. The forms of the violation of co-operative maxims are quantity, quality, relevance, and manner. The forms of the violation of politeness maxims are tact, approbation, modesty, agreement, and sympathy. The easier way to understand comics is reading verbal and nonverbal forms.